(3QSGdI GdRGjQLIs - (3HgGAGdOjfs ((3eMeO Hf WGgQ GdSeGhj s)
(3ChdgG (B:s
(3gPg JdNjU GdRGjQLI GdJj hVYgG CHhGdYHGS GdSHJj aj GdLaQ QJHJgG Ydi ebOeI hebUO hNGJeI s
(3BNQgG (B:s
(3hLfHfG ef GdRdd hNJe dfG HCMSf GdYde hGdYed Efg hdj GdYhGbH hHjOg CReI GdeWGdH JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdRjQLI dGHf GdHfG GfXQ cTa GdXfhf L (B2 (3U` (B949s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs